Perilaku Hidup Bersih dan Sehat Siswa SLB Tegar Harapan - Unan Yusmaniar Oktiawati; Wulansari Irjaya Kusumaputri; Alfian Kemal; Rafi Irsyad Fakhrheza; Syifa Nabiel Hadera; Hutami Pratiwi; Saphira Fawwazul Atsiri; Ammarissa Alya Tsabita; Muhammad Ikhsanuddin Noor; Adhitya Nur Mahendra; Bernadette Tisa Anggita; Rizkhal El-Ikhran; Muhammad Arindra Saka Pritama; Maura Andini Setiabudi; Sri Kumala Dewi; Cici Yulian Anugraheni; Mardiyah Desy Romadhoni; Annisa Irba Fadhila (Direktorat Pengabdian kepada Masyarakat, 2026)
Clean and Healthy Living Behavior (Perilaku Hidup Bersih dan Sehat/PHBS) is an essential component in improving student’s health status in the school environment. The implementation of PHBS from an early age plays a crucial role in preventing various diseases related to personal hygiene. However, the application of PHBS among children with special needs often faces challenges due to limitations in cognitive, motoric, and sensory aspects. Preliminary observations at SLB Tegar Harapan indicated that most students had not been able to practice proper handwashing as part of PHBS at School. This paper presents activity to improve the knowledge and skills of students at SLB Tegar Harapan in performing proper handwashing behavior. The method used was a descriptive approach with an educational intervention through simple health education and hands-on practice. The activities were conducted in several stages, including initial observation, delivery of health education using visual media and teaching aids, handwashing demonstrations, repeated practice, and evaluation of students' abilities after the intervention with teacher assistance. The results showed an improvement in students’ ability to perform proper handwashing steps after receiving education and guidance. Behavioral changes were also observed, as indicated by an increased habit of handwashing before and after school activities, although some students still required assistance. In addition, teacher involvement played an important role in strengthening the sustainable implementation of Clean and Healthy living Behavior (PHBS). This study concludes that PHBS education delivered through demonstration and continuous guidance is effective in improving handwashing behavior among students with special needs. Support from the school environment and consistent assistance are essential to gradually develop clean and healthy living habits.